From the Work Concept to Hypermusic: Rethinking Musical Objects in-and-for Blockchain Technologies - Assis, Paulo de (Boca Raton CRC Press, Taylor & Francis Group, 2024)
The practice of music - be it its composition, interpretation, performance, or listening - is deeply intertwined with the medium through which it is generated, transmitted, and preserved. Historically, music rooted in oral traditions relied heavily on human memory, passing down nuances through generations without the need for written notation. The advent of musical scores marked a shift, envisioning music as a textual entity that could be inscribed, interpreted, and realized in various forms. With the introduction of recordings, music assumed the character of fixed time-bound segments, capturing and preserving sonic events as permanent artifacts. The digital era further transformed music into retrievable data, subject to computational analysis and rendering, managed by specialists in digital humanities. In this evolving landscape, blockchain technologies have the potential to offer yet a new profound redefinition of music, portraying it as a constellation of infinite particles. This new medium facilitates not only human interaction but also algorithmic and computational participation, allowing for endless recombinations and creations in the musical landscape. This evolution of mediums reflects an ongoing redefinition of what music is and can be, with blockchain opening new horizons for understanding and creating music.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music